Insufficiency fracture in normal pressure hydrocephalus – A case report - Biswas, Ratnashree; Chakraborty, Nilanchal (Indian Journal of Case Reports, 2026)
Idiopathic normal pressure hydrocephalus (iNPH) is a progressive neurological disorder in the elderly, marked by gait disturbance, cognitive decline, and urinary incontinence. This case report describes a 77-year-old male with untreated iNPH who developed a spontaneous insufficiency fracture of the proximal femur without any history of trauma. Investigations revealed Vitamin D deficiency, secondary hyperparathyroidism, and early signs of chronic kidney disease, contributing to compromised bone health. Prolonged immobility due to iNPH likely exacerbated bone demineralization and muscle atrophy, increasing fracture risk. Surgical intervention was chosen over conservative management to facilitate early mobilization and prevent complications. This case underscores the need for heightened clinical vigilance for insufficiency fractures in cognitively impaired, immobile elderly patients and highlights the importance of proactive nutritional and metabolic bone health management in those with iNPH.